Pengaruh Implementasi Sistem Informasi Akuntansi dan Digital Accounting terhadap Efisiensi Operasional dengan Kompetensi SDM sebagai Variabel Mediasi di Kota Medan - Ayu Andira; Fachrun Nissa; Rahmad Dani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the effect of Accounting Information System (AIS) implementation and digital accounting on operational efficiency, with human resource (HR) competency as a mediating variable in Micro, Small, and Medium Enterprises (MSMEs) in Medan City. This research employed a quantitative approach using a causal associative method. Data were collected through questionnaires distributed to MSME owners using purposive sampling techniques and were analyzed using Partial Least Square-based Structural Equation Modeling (SEM-PLS). The results indicate that digital accounting has a positive and significant effect on operational efficiency. HR competency is also proven to have a positive and significant effect on digital accounting and operational efficiency, both directly and indirectly through its mediating role. Meanwhile, the Accounting Information System has a positive effect on digital accounting, but directly shows a negative effect on operational efficiency. However, through the mediation of digital accounting, AIS provides a positive effect on operational efficiency. These findings indicate that improving MSMEs’ operational efficiency depends not only on the adoption of technology but is also strongly influenced by the competency of human resources in operating and utilizing these systems. Therefore, enhancing HR capacity and optimizing the integration of digital-based accounting systems are important strategies to support the digital transformation of MSMEs.